Living history: Reading Edmund Burke on representation. Issue 3 (December 2015) - Bourke, Richard
Abstract : 250 years on, Richard Bourke traces the development of Edmund Burke's sophisticated conception of representation, one which stands in stark contrast to simplistic notions of 'being like us' which permeate our modern debates about political authority and democratic legitimacy.